Otimização da produção e modelagem in silico de celulase de uma linhagem marinha de Bacillus subtilis halotolerante - Santos, Yago Queiroz dos (2020)
The current demand for renewable and ecological energy sources has boosted the search for alternatives capable of replacing the use of fossil fuels. One of the most promising innovations to positively impact the world energy scenario is the production of second generation bioethanol (2G-ethanol) from reducing sugars derived from the enzymatic degradation of lignocellulosic material that is normally discarded in agro-industrial processes. Cellulose is the most abundant linear homopolysaccharide on the planet formed by glucose units linked by β- (1-4) glycosidic bonds. This work aimed at structural modeling and the establishment of enzymatic bioprocesses optimized for the conversion of processed lignocellulosic material into fermentable reducing sugars. After the optimization process, the maximum practical yield obtained was 7.30% higher than the initial condition, reaching an enzymatic activity of 318.809 ± 0.784 U / mL while in silico modeling showed the presence of a monomeric structure in the main endoglucanase involved in the process. According to the data obtained in this work, it was possible to conclude the possibility of applying this optimized bioprocess in industrial processes for the generation of bioethanol.